Effective Counterterrorism: What Have We Learned so Far? - Eric van Um; Daniela Pisoiu (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The fight against terrorism, in particular of Islamist nature, has become a focus area of foreign and security policies in Western countries and around the world. This substantial effort is however only to a limited extent matched by adequate evaluations as to its actual success. This paper offers an overview of the counterterrorism effectiveness literature in terms of main areas of interest, conceptualisation and operationalisation difficulties as well as methodological considerations regarding the types of methods used, validity and reliability evaluations. It discusses the different understandings of causality and proposes a working definition of counterterrorism effectiveness. We find that a main focus of the literature lies on the impact component of effectiveness, often in the sense of a reduction of terrorist attacks in general or a reduction of certain methods of terrorism such as suicide attacks. Our model article "What Happened to Suicide Bombings in Israel? Insights from a Terror Stock Model" by Kaplan et al. (2005) illustrates the above-mentioned issues and reflects the mainstream approach in this field. The article uses econometric methods to determine the impact-effectiveness of counter-terrorism and reflects the problematique associated with attempts to infer a causal relationship between counterterrorism policies and the occurrence of terrorism.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330; Counterterrorism; effectiveness; causality; quantitative and qualitative research methods